Ragam Bahasa Pada Interaksi Jual Beli Di Pasar Rakyat Malino Kabupaten Gowa - Mizwar Wahyudi; Abd.Rahman Rahim; Abd Munir (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research uses a qualitative approach. The data for this research are speech obtained from speech events between sellers and buyers at the Malino People's Market, Gowa Regency. Language is the object of research and language use (sellers and buyers) is the subject of this research. The data source is the speech of sellers and buyers, which occurred in buying and selling transactions at the Malino People's Market, Gowa Regency, which were carried out from December 2022 to January 2023. The method used to collect data was the observation, listening, recording and note-taking method. Data analysis was carried out by adhering to a flow model data analysis flow which includes four activity steps, namely (1) data collection, (2) data reduction, (3) data presentation, and (4) conclusion/verification. The research results show that (1) The variety of buying and selling languages ​​at the Malino People's Market, Gowa Regency consists of (a) Sellers and buyers use Makassar language; (b) Sellers and buyers use the Makassar dialect of Indonesian; (c) Sellers and buyers use Bugis language; (d) The seller uses the Makassar dialect of Indonesian and the buyer uses the Jakarta dialect of Indonesian; (e) Sellers and buyers use the Jakarta dialect of Indonesian; (f) The seller uses Makassar language and the buyer uses Indonesian; (g) The seller uses Makassar language instead of Indonesian and the buyer uses Indonesian; (h) The seller uses Makassar language instead of Bugis language and the buyer uses Bugis language; (i) Sellers and buyers use a code-mixed language of Makassar or Bugis and Indonesian. (2) The interaction pattern in buying and selling interactions at the Malino People's Market, Gowa Regency consists of (a) transaction objectives; (b) the relationship between the seller and the buyer is personal: (c) bargaining; (d) the seller in his interaction develops verbal persuasion; (e) buyers in interactions develop verbal persuasion. (3) The speech levels of sellers and buyers in buying and selling interactions at the Malino People's Market, Gowa Regency consist of high, medium and medium levels.